1994
DOI: 10.1002/jez.1402690206
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes accompanying the acquisition of meiotic competence in ovarian goat oocyte

Abstract: In order to determine at which follicular size goat oocytes were capable of resuming and completing meiosis, we evaluated their ability to mature in vitro and measured their maturation promoting factor (MPF) activity by histone H1 kinase assay. The results indicated that goat oocyte meiotic competence developed progressively in follicles ranging from 0.5 to 3 mm; the oocytes acquired the ability to resume meiosis in follicles of 0.5-0.8 mm, to reach metaphase I (MI) in follicles of 1-1.8 mm, and to reach metap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 37 publications
7
43
0
Order By: Relevance
“…The incidence of Mil (15%-30%) in smaller size follicles was quite comparable to a host of other reports for this species (Nickson et al, 1993;Yamada et al, 1993;Otoi et al, 2001;Willingham-Rocky et al, 2003). At the same time, the positive impact of larger follicle size in the dog was analogous to findings in other mammals, including the goat (De Smedt et al, 1994;Crozet et al, 1995), pig (Christmann et al, 1994), cow (Lonergan et al, 1994;Pavlok et al, 1997), and horse (Goudet et al, 1997). In fact, the common denominator for all of these species is that oocytes have more capacity to complete nuclear maturation when the host follicle is >2 mm in diameter.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The incidence of Mil (15%-30%) in smaller size follicles was quite comparable to a host of other reports for this species (Nickson et al, 1993;Yamada et al, 1993;Otoi et al, 2001;Willingham-Rocky et al, 2003). At the same time, the positive impact of larger follicle size in the dog was analogous to findings in other mammals, including the goat (De Smedt et al, 1994;Crozet et al, 1995), pig (Christmann et al, 1994), cow (Lonergan et al, 1994;Pavlok et al, 1997), and horse (Goudet et al, 1997). In fact, the common denominator for all of these species is that oocytes have more capacity to complete nuclear maturation when the host follicle is >2 mm in diameter.…”
Section: Discussionsupporting
confidence: 88%
“…In other mammals, oocyte meiotic and developmental competence is progressively acquired during follicular growth (Christmann et al, 1994;DeSmedtetal., 1994;Lonerganetal., 1994;Crozetetal., 1995;Goudet et al, 1997;Pavlok et al, 1997). For example, in the goat, oocytes from follicles of 0.5-0.8 mm in diameter are only able to begin meiotic resumption, whereas those from follicles of 1•1.8 mm are capable of meiotic progression to metaphase I (MI), while those from follicles >3 mm are able to reach Mil (De Smedt et al, 1994). Unlike in the cow, goat, pig, or cat, dog follicles generally remain below the ovarian surface within the cortex and are not visible until late proestrus (Wildt et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of histone H1 by cellular extracts forms the basis of an assay used to determine the level of MPF activity during meiosis and mitosis [90]. Changes in the level of MPF activity have been found to be similar during maturation of mouse [96,97], rabbit [98], goat [99], cattle [100][101][102] and pig [103][104][105][106][107] oocytes. Numerous studies have found that the level of MPF activity is relatively low at the germinal vesicle stage and steadily increases as meiosis progresses to the first metaphase (M-I) stage.…”
Section: Maturation-promoting Factormentioning
confidence: 99%
“…Moreover, the meiotic competence in bovine species is closely related to the follicular dimension; oocytes derived from small follicles showed a lower capacity to resume meiosis and to develop up to early embryonic stages [4]. Previous works [8,19,23] [9,26,27]. This can be related to defective conditions of oocyte maturation and can also be due to the reduced size of oocytes and follicular population [17] and a small size of volume fractions of mitochondria and cortical granules [25].…”
mentioning
confidence: 98%